2020
DOI: 10.31703/gssr.2020(v-i).09
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Accreditation in Assuring the Quality of Teacher Education Programs: Exploring the Case of an Underdeveloped Country

Abstract: This study examined the effectiveness of an accreditation mechanism for teacher education exclusively with a fragile higher education system in Pakistan. A quantitative research method was employed. Using the stratified technique, 614 participants from 24 higher education institutions were selected. Questionnaires were used to collect data from participants. The findings revealed that the standards of national accreditation council for teacher education (NACTE) cannot win wide acceptability and support of educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…On the contrary, few researchers have found a partial or insignificant effect of accreditation in ensuring the quality of programs and the attributes development of graduates in Pakistani universities (Jalal et al, 2017). According to Jalal et al (2020), NACTE accreditation mechanism for teacher training is less effective in providing adequate, modern and quality education to teachers in Pakistan. Similarly, Dattey et al (2017) have found that accreditation has no impact on the quality of the curriculum, faculty employment, studentstaff ratio, or library facilities.…”
Section: Accreditation and Higher Education Performancementioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, few researchers have found a partial or insignificant effect of accreditation in ensuring the quality of programs and the attributes development of graduates in Pakistani universities (Jalal et al, 2017). According to Jalal et al (2020), NACTE accreditation mechanism for teacher training is less effective in providing adequate, modern and quality education to teachers in Pakistan. Similarly, Dattey et al (2017) have found that accreditation has no impact on the quality of the curriculum, faculty employment, studentstaff ratio, or library facilities.…”
Section: Accreditation and Higher Education Performancementioning
confidence: 99%
“…Despite these benefits, previous studies have shown inconsistent results. Some studies have revealed the positive effects of accreditation on different aspects of higher education, such as teaching, learning, quality and management activities (Nguyen and Ta, 2017; Makhoul, 2019; Kumar et al ., 2020); while few studies have found an insignificant or negative relationship with teaching/learning and the quality of HEIs (Dattey et al ., 2017; Jalal et al ., 2017; Jalal et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, few researchers have opined that accreditation has a partial or insignificant role in ensuring the quality of programs and attribute development of graduates in Pakistani universities (Jalal et al, 2017). Another study revealed that the NACTE accreditation mechanism for teacher training in Pakistan is less effective in providing adequate, modern and quality education to teachers (Jalal et al, 2020). While for others, accreditation has no impact on curriculum quality, faculty employment, student-staff ratio, and library facilities (Dattey et al, 2017).…”
Section: Accreditation and Higher Education Performancementioning
confidence: 99%
“…Previously, scholars have attempted to investigate accreditation in the context of HE, however results are inconsistent. Some studies have found a positive role of accreditation in relation to different aspects of HE (Kumar et al, 2020;Makhoul, 2019;Nguyen & Ta, 2017); while few studies have found an insignificant or negative effect of accreditation with teaching/learning and quality of HEIs (Dattey et al, 2017;Jalal et al, 2017Jalal et al, , 2020. However, majority of the previous work on accreditation is qualitative in nature, and thus there is no conclusive empirical evidence of accreditation in relation to higher education performance.…”
Section: Introductionmentioning
confidence: 99%
“…The problem addressed by the study is twofold. On one level, there is a clear evidence that implementing specific accreditation procedures improves both quality of teacher education and its public and professional outlook (Jalal et al, 2020;Makhoul, 2019;Murray, 2000;Qin, 2021;Solbrekke & Sugrue, 2014). The general image of teaching as a profession in Russia is believed to be quite bleak (Lyubimov, 2005), though it is yet unchallenged on the grounds of quality of teacher training.…”
Section: Problem Statementmentioning
confidence: 99%